Breathing exercise and chest physiotherapy in post-acute COVID-19 patient: a case report - Nyoman Chandra Adidharma; Bagus Diva Indra Dharma; Kade Ngurah Dwi Putra Negara; I Gede Adi Sudewa (DiscoverSys Inc., 2022)
Background: Severe acute respiratory syndrome (SARS CoV2) and coronavirus disease 2019 causes vary from mild to severe clinical manifestation. Complications from COVID-19 can show several manifestations such as pulmonary, cardiovascular, neuromuscular, and renal systems, which could lead to multi-organ failure. Lung fibrosis and recurrent pneumonia are some of some sequelae of survivors, and some need readmission to hospital, although the PCR swab test remains negative. Post-acute COVID-19 is a syndrome characterized by persistent clinical symptoms beyond four weeks from the onset of acute symptoms. Case: In this writing, a 57-year-old male presented with chief complaints of shortness of breath and cough 2 days after being discharged from the hospital because of a COVID-19 infection. His PCR swab test result remains negative when readmission. The patient was on non-invasive ventilation, medical therapy and physical therapies such as breathing exercises and chest physiotherapy. The physical therapy was done twice daily. On the seventh day of exercise, the shortness of breath was improved, and NIV was tapered down. The patient was discharged after 27 days of hospitalization. Conclusion: This case shows the benefit of breathing exercises and chest physiotherapy for the Post-acute COVID-19 patient. This helps improve respiratory muscle strength and chest expansion in order to improve oxygen perfusion.